Unisonance in singing Malaysian popular patriotic songs: bridging collective integration through music - Shazlin A. Hamzah, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The line between popular and nationalist music is hazy because any musical style or repertoire has the potential to express nationalism given the right environment and circumstances. Yet, singing and listening to it never misses its aim because the language of song is the most widespread way in which music signifies the nation.1 The unified singing of anthems and patriotic songs done together by a group of people usually not known to each other is called ‘unisonance’2 and can result in an emotionally overwhelming feeling of collective cohesion. Focus group discussions on local popular music listening were conducted in 2019 throughout Kota Kinabalu, Kuching and Klang Valley. This paper discusses findings surrounding data drawn from this research focusing on respondent’s reactions towards patriotic songs. Findings suggest that Malaysians enjoy listening to and singing patriotic songs individually and more importantly, in concert, as they are a verbal way of manifesting love for the country. Of paramount point here is it creates a moment of unisonance for them, a simultaneous and unanimous acknowledgment of the common symbol, that is the song – over and above any racial or cultural trait – that signifies belonging and begets collective emotional commitment.